Synthesis and characterization of poly(1,3-thiazol-2-yl-carbomoyl) methyl methacrylate: Its metal complexes and antimicrobial activity studies - Soykan, C; Erol, I; Kirbag, S (John Wiley & Sons Inc, 2003)
Poly(1,3-thiazol-2-yl-carbomoyl) methyl methacrylate [poly(TCMMA)] is prepared in dimethyl sulfoxide using 2,2'-azobisisobutyronitrile as an initiator at 60degreesC. Poly(TCMMA) is characterized by IR and H-1-NMR spectroscopic techniques. Cadmium(II), copper(II), and nickel(II) chelates of poly(TCMMA) were synthesized. An elemental analysis of the polychelates suggests a metal/ligand ratio of 1:2. The polychelates are further characterized by IR and magnetic susceptibility measurements. The thermal properties of the polymer and metal chelates are also discussed. The molecular weights of the poly(TCMMA) are determined by the gel permeation chromatography technique. The antimicrobial activities of the polymer and metal chelates are tested against Staphylococcus aureus COWAN I (bacteria), Escherichia coli ATCC 25922 (bacteria), Listeria monocytogenes SCOTTA (bacteria), Bacillus subtilis LMG (bacteria), Enterobacter aeroginosa CCM 2531 (bacteria), Klebsiela pneumania FMCS (bacteria), Candida albicans CCM 314 (Mayo yeast), and Saccharamyces cerevisiae UGA 102 (Mayo yeast). (C) 2003 Wiley Periodicals, Inc.
Keywords: poly(1,3-thiazol-2-yl-carbomoyl) methyl; methacrylate; metal-polymer complexes; radical polymerization; thermal properties; antimicrobial activities